2001
DOI: 10.1073/pnas.201387198
|View full text |Cite
|
Sign up to set email alerts
|

Binding of cyclin-dependent kinases to ORC and Cdc6p regulates the chromosome replication cycle

Abstract: Cdc6p and the origin recognition complex (ORC) are essential for assembly of a pre-replicative complex (preRC) at origins of replication, before the initiation of DNA synthesis. In the absence of Cdc6p, cells fail to initiate DNA replication and undergo a ''reductional'' mitosis, in which the unreplicated chromosomes are randomly segregated to the spindle poles. We show here that the cells harboring a mutation in the essential Cdc6p Walker A-box arrest in late mitosis, probably at anaphase. This cell cycle blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 78 publications
2
68
0
1
Order By: Relevance
“…This idea is in agreement with Palacios DeBeer et al (2003), who demonstrate that origin and HM silencer ACS differ in their affinity for the ORC and that this difference reflects the preferential function of the corresponding ACS in silencing or origin firing. We propose that an additional functional dissimilarity of these two types of ACS is their dependence on the cdc6-1 allele (Figure 3) (Weinreich et al 2001;Tsuyama et al 2005). It is possible that the surrounding sequence of core X-and Y9-elements influences the ACS silencing specificity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This idea is in agreement with Palacios DeBeer et al (2003), who demonstrate that origin and HM silencer ACS differ in their affinity for the ORC and that this difference reflects the preferential function of the corresponding ACS in silencing or origin firing. We propose that an additional functional dissimilarity of these two types of ACS is their dependence on the cdc6-1 allele (Figure 3) (Weinreich et al 2001;Tsuyama et al 2005). It is possible that the surrounding sequence of core X-and Y9-elements influences the ACS silencing specificity.…”
Section: Discussionmentioning
confidence: 94%
“…Cdc6p is essential for the loading of the MCM complex on ORC-bound ACS at origins of replication (Blow and Dutta 2005). The cdc6-1 allele impairs DNA replication (Weinreich et al 2001;Tsuyama et al 2005). However, it selectively caused derepression only in the ACS-less GF2 and GF3 constructs, while having negligible effects on the ACS-containing constructs ( Figure 3G).…”
Section: Discussionmentioning
confidence: 99%
“…The former function mapped to the essential domains of Cdc6p that are structurally related to Orc1p and other AAA ϩ proteins (18,33,43,54). The latter function mapped to the amino terminus, suggesting that Cdc6p controls the G 1 /S transition and also the G 1 /M checkpoint (18,55,56). Genetic analysis in S. pombe suggested that it restricts the initiation of DNA replication to once per cell cycle (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…The fidelity of these processes is dependent on precise chromosome duplication and segregation (once-per-cell cycle replication), spindle pole body duplication and separation, nucleus migration, cytokinesis, etc. (31)(32)(33). However, mutations conferring defects in these processes results in autopolyploidy (increase in ploidy that originates by the multiplication of one basic set of chromosomes) (34,35).…”
Section: The Endoplasmic Reticulum (Er)mentioning
confidence: 99%